2021
DOI: 10.1111/gwao.12614
|View full text |Cite
|
Sign up to set email alerts
|

A gendered pandemic: Childcare, homeschooling, and parents' employment during COVID‐19

Abstract: The COVID-19 pandemic has dramatically affected employment, particularly for mothers. Many believe that the loss of childcare and homeschooling requirements are key contributors to this trend, but previous work has been unable to test these hypotheses due to data limitations.This study uses novel data from 989 partnered, US parents to empirically examine whether the loss of childcare and new homeschooling demands are associated with employment outcomes early in the pandemic. We also consider whether the divisi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
312
1
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 316 publications
(327 citation statements)
references
References 57 publications
9
312
1
5
Order By: Relevance
“…Mothers' labor force participation was less affected in states that offered hybrid or in‐person instruction (Collins et al., 2021). These patterns highlight how additional responsibilities associated with online schooling particularly impacted mothers' employment and align with a non‐representative study of about 1000 U.S. parents, which found that women were more likely than men to drop out of the labor force, if they were responsible for creating all or some of the school content (Petts et al., 2021).…”
Section: The Pandemic and Gender Inequality: Changes To Work And Familysupporting
confidence: 66%
See 2 more Smart Citations
“…Mothers' labor force participation was less affected in states that offered hybrid or in‐person instruction (Collins et al., 2021). These patterns highlight how additional responsibilities associated with online schooling particularly impacted mothers' employment and align with a non‐representative study of about 1000 U.S. parents, which found that women were more likely than men to drop out of the labor force, if they were responsible for creating all or some of the school content (Petts et al., 2021).…”
Section: The Pandemic and Gender Inequality: Changes To Work And Familysupporting
confidence: 66%
“…Additionally, given that men infrequently drop out of the labor market for childcare reasons (Livingston, 2018), childcare facilities and schools provide critical institutional support that enables women's working abilities (Ruppanner, Moller, & Sayer, 2019). The COVID‐19 pandemic and its associated mitigation measures, however, brought wide‐spread disruptions to childcare and schooling arrangements, affecting millions of parents and their paid and unpaid labor (Collins et al., 2021; Patrick et al., 2020; Petts et al., 2021). 2…”
Section: The Pandemic and Gender Inequality: Changes To Work And Familymentioning
confidence: 99%
See 1 more Smart Citation
“…The unprecedented disruptions created an unusual opportunity, akin to a natural experiment, to see how an external shock that upended usual employment practices affected paid and unpaid work. Around the world, early findings showed that the restrictions not only created much more household labor and care, but also that men were doing more of this unpaid work alongside women (Carlson, Petts, and Pepin 2020;Sevilla and Smith 2020). This was also the case in Australia Churchill 2020a, 2020b).…”
mentioning
confidence: 99%
“…) and, on a personal basis, separation/isolation from family (ONS, 2020). Separation and isolation create significant challenges for family life, with increasing inequality and poverty (Power, 2020;Van Lancker & Nieuwenhuis, 2020), domestic violence (Sharma & Borah, 2020), and reduced labour force participation (Petts et al, 2021). These challenges can significantly affect economic stability, which is heightened as individuals experience unemployment and economic inactivity.…”
mentioning
confidence: 99%